Premixed flame acceleration in straight and bend close pipe - Miss Hasimawaty, Mat Kiah (2013)
There were many studies on premixed flame propagation in tubes, including open tubes and enclosures. Yet, no sufficient data obtained for explosion properties in medium scale piping system to assist engineers or practitioners in determining the potential hazard posed due to explosion. In this work, an experimental study had been carried out to investigate the explosion properties in a pipeline using two pipe configurations, i.e. straight and 90 degree bend. A horizontal steel pipe, with 2 m long (L) and 0.1 m diameter (D), giving L/D ratio of 20 was used in the range of equivalence ratios (Ф) from 0.5 to 1.8. The 90 degree bend pipe had a bend radius of 0.1 m with added a further 1 m to the length of the pipe (based on the centerline length of the segment). Natural gas/pure oxygen mixture was prepared using partial pressure method and a homogeneous composition was achieved by circulating the mixture using a solid ball which was placed in the mixing cell. It was shown that stoichiometric mixtures gave the highest flame speed measurement, both on straight and bend pipes. Stoichiometric concentration (Ф = 1.0) gave significant maximum overpressure of 5.5 bars for bend pipe, compared to 2.0 bars on straight pipe explosion test; approximately 3 times higher. This was due to bending part that acted like obstacles. This mechanism could induce and created more turbulence, initiated the combustion of unburned pocket at the corner region, causing high mass burning rate and hence, increased the flame speed. It was also shown that the flame speed was enhanced by factor of 3 for explosion in bend pipe compared to straight pipe. It can be concluded that the bend can create greater turbulence effect compared to straight pipe configuration and applying appropriate safety devices before the area of the bends is recommended as one of the effective methods to prevent the explosion from happen.